ANALISIS MANAJEMEN RANTAI PASOK BENIH JAMBU METE (STUDI KASUS DI KABUPATEN FLORES TIMUR) - Hasibuan, Abdul Muis; Wahyudi, Agus (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Supply chain management analysis of cashew seed (Case study in the district of East Flores). East Flores is sourced reference ofsuperio cashew seeds, so that this region is potentially a superior seed producer of cashew for development program in the future. This study aimed toanalyze supply chain management (SCM) and development strategy of cashew superior seed. The research was conducted in East Fl ores, East NusaTenggara Province in June - August 2010. The data used are primary and secondary data. Analysis used model of supply chain management. Theresults showed that the demand for cashew seed is dependent on the procurement project undertaken by the government. The time often not coincidewith the harvest of cashew seeds. Supply chain management applications has been running optimal although more are caused by g overnmentintervention in terms of distribution of seeds, so that the optimization process of SCM has not been produced from a process of good business activity.Strategies that can be achieved are: (i) government needs to encourage the process of seed certification by an official agency, (ii) developing the seedgarden in an amount sufficient to consider the projected seed demand in the future, either in the form of seeds and scion, (iii) the farmer / farmergroup, the owner of seed source should be able to apply the seed stock management so that demand outside the crop seed remain to be fulfilled, (iv) thebreeder needs to make improvements in a poly bag seed distribution methods, (v) The Government needs to introduce grafting technology, particularlyto the breeder and farmer groups, (vi) The Government needs to do the planning and mapping needs and promoting improved s eed varieties MPF 1.